Balance hídrico e hidrológico de la Cuenca Alta del río Gállego - Marín Jaime, José María (Geographicalia, 2017)
Located in the Spanish side of the Pyrenees the Gallego river is one of the mayor tributaries to the Ebro river basin right margin. This paper analyses the hydric balance of Gallego's upper basin, indicating the work-methodology which has helped us in its establishment.